2015
DOI: 10.1016/j.ijcme.2015.02.002
|View full text |Cite
|
Sign up to set email alerts
|

Physiology of oxygen uptake kinetics: Insights from incremental cardiopulmonary exercise testing in the Study of Health in Pomerania

Abstract: BackgroundCardiopulmonary exercise testing allows for assessment of cardiac and respiratory limitation, but is often affected by patient effort. Indices of oxygen kinetics, including the oxygen uptake efficiency slope (OUES), oxygen uptake–work-rate slope (VO2–WR slope) and the heart rate–oxygen uptake slope (HR–VO2 slope) are relatively effort independent but may be affected by patient characteristics.The objective of this study is to identify the impact of factors, such as age, gender, body size, respiratory… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
17
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(20 citation statements)
references
References 26 publications
3
17
0
Order By: Relevance
“…In our trial, NT-proBNP levels were better correlated with CPET parameters in females compared to males. In general, exercise capacity is gender dependent [ 11 ], probably reflecting differences in muscle mass [ 12 ] or myocardial geometries and functions [ 13 ]. Recently, a study by Swift and colleagues [ 14 ] demonstrated that male PAH patients have proportionally worse right heart function despite a similar afterload compared to females.…”
Section: Discussionmentioning
confidence: 99%
“…In our trial, NT-proBNP levels were better correlated with CPET parameters in females compared to males. In general, exercise capacity is gender dependent [ 11 ], probably reflecting differences in muscle mass [ 12 ] or myocardial geometries and functions [ 13 ]. Recently, a study by Swift and colleagues [ 14 ] demonstrated that male PAH patients have proportionally worse right heart function despite a similar afterload compared to females.…”
Section: Discussionmentioning
confidence: 99%
“…Maximal voluntary ventilation (MVV) was calculated as: 40 · forced expiratory volume in 1 s (FEV 1 ). Predicted values for peak VO 2 and OUES were generated from the SHIP study 13 , 14 . All other calculations were performed using standard methods.…”
Section: Methodsmentioning
confidence: 99%
“…The percent predicted oxygen uptake efficiency slope (OUES) was calculated using data from Barron et al. (14) . COPD = chronic obstructive pulmonary disease; VO 2 = oxygen uptake.…”
Section: Figurementioning
confidence: 99%
“…No results in adults were found. Five studies reported oxygen uptake efficiency slope (OUES) values, two in adults [42,43], two in a pediatric population [29,34], and one study reporting up to young adulthood (21 years of age) [44].…”
Section: Breathing Frequency At Peak Exercisementioning
confidence: 99%